Nipah Virus Encephalitis: Pathogenetic Aspects and Current Therapeutic Strategies - Gaetano Scotto; Vincenzina Fazio; Ali Muhammed Moula; Sri Charan Bindu Bavisetty; Alessia Franza; S. Massa (Pathogens, 2026)
Nipah virus (NiV) is a highly pathogenic zoonotic paramyxovirus responsible for sporadic outbreaks of severe disease with high case fatality rates in South and Southeast Asia. Human infection occurs through spillover from natural reservoirs, primarily fruit bats, or via human-to-human transmission, and is characterized by a broad clinical spectrum ranging from asymptomatic infection to acute respiratory disease and fatal encephalitis. Following entry via ephrin-B2 and ephrin-B3 receptors, NiV exhibits marked endothelial and neuronal tropism, leading to systemic vasculitis, disruption of the blood-brain barrier, and direct infection of the central nervous system. Disease progression is driven by a complex interplay between viral replication strategies and host immune responses. NiV effectively counteracts innate immunity through multiple viral proteins that inhibit interferon signaling, while simultaneously inducing dysregulated inflammatory responses that contribute to tissue damage and multi-organ failure. Neurological involvement represents the most severe manifestation, often resulting in acute or relapsing encephalitis with long-term sequelae among survivors. Despite the severity of the disease, no licensed antiviral therapies or human vaccines are currently available. Therapeutic development has focused on neutralizing monoclonal antibodies targeting viral glycoproteins and small-molecule antivirals that inhibit viral RNA synthesis, both of which show promising results in preclinical models, but remain limited by timing and translational challenges. In parallel, several vaccine platforms-including viral vectors, mRNA-based constructs, and recombinant protein subunits-have advanced to early-phase clinical trials, demonstrating encouraging immunogenicity. Beyond biomedical interventions, effective outbreak containment relies on integrated public health strategies. The "Kerala model" highlights the importance of rapid case identification, isolation, contact tracing, and community engagement within a One Health framework to mitigate transmission and reduce mortality. This review synthesizes the current knowledge on NiV pathogenesis, immune evasion, clinical manifestations, and emerging therapeutic and vaccine strategies, while highlighting critical gaps and future directions for improving the preparedness and response to this high-consequence emerging pathogen.
Keywords: Virology and Viral Diseases; Immune responses and vaccinations; Mosquito-borne diseases and control